The Relationship between Principals' Competencies in Budgeting and Performance of Financial Management Roles in Public Secondary Schools in Kenya - Pius Kipruto Kosgei; Mapheleba Lekhetho (Social Sciences and Education Research Review, 2025)
The study investigated the relationship between the principals' budgeting competencies and the performance of selected financial management roles in public secondary schools in Kajiado County, Kenya. It combined Scientific Management Theory (SMT) and systems theory to form a strong theoretical framework. It adopted a quantitative methodology using a correlational research design and a qualitative methodology using a case study design. Data from principals and bursars was collected through questionnaires, while semi-structured interviews were used for school auditors. The study used a multistage sampling technique to select a sample of 115 public secondary school principals and 111 school bursars, while three school auditors were selected purposively. The findings indicate that there was a positive and statistically significant relationship between the principals' budgeting competencies and their performance of financial management roles; They also indicate that some principals did not have the necessary budgeting competencies to prepare budgets on time, interpret the budgets regularly, guide the heads of departments in budget making, link school development plans to their budgets and prepare comprehensive budgets. The study recommends that principals be trained, mentored and coached in comprehensive budget preparation and interpretation, and school development plans should be linked to budgets. They should also be trained, mentored and coached in monitoring budget implementation and aligning budgets with vote heads to address the competency and skills gaps.